RESULTS OF SURGICAL TREATMENT OF A PANCREATIC HEAD TUMOR COMPLICATED BY MECHANICAL JAUNDICE. - G.N. Rayimov; N.A. Salokhiddinov; J.R. Kholmukhamedov; A.R. Tillaboldiyev; Sh.Sh. Dexqonov (Scholar Express Journals, 2023)
The development of new technological solutions for palliative surgical treatment of patients with unresectable pancreatic head cancer is an urgent task, since the frequency of postoperative complications in such patients reaches 25%, and the mortality rate is 20%.
Keywords: mechanical jaundice